Impact of Cluster Front Line Demonstrations on Field Pea (Pisum sativum L.) in valley areas of Manipur (Indian Journal of Extension Education, 2022)
In Imphal district of Manipur, the field pea (Pisum sativum L.) is a prominent rabi season pulse crop. In comparison to other sections of the country, however, its output is quite poor. The productivity and economics of cluster front line demonstrations, as well as the adoption of newest production technologies including technology and extension gap by 50 Cluster Front Line Demonstrations (CFLD) farmers and 50 non-CFLD farmers were investigated during 2018-19 to 2020-21. The results revealed that average yield of the demonstration were 15.33 q/ha against the potential yield of 22 q/ha. The yield gap of 6.67 q/ha indicates that there still a technology gap and still there is big scope for increasing the yield. The percentage of increase in yield in CFLD ranged from 38.43 to 40.17 per cent with an average increase of 39.57 per cent over the farmers practice in local check plots. The extension yield gap fluctuated between 27.97 and 28.64 per cent. Overall it is concluded that cluster frontline demonstrations (CFLD) proved an effective tool for increasing the productivity of field pea.